Implementasi Metode Double Diamond Design Untuk Redesain Antar Muka Aplikasi SBS Exam Pada Smp Negeri 3 Waru - Alam, Yholandha Martha Rhisma; Wulandari, Sri Hariani Eko; Wahyuningtyas, Nunuk (Jurnal Sistem Informasi Universitas Dinamika, 2021)
SMP Negeri 3 WARU is a Ministry of Education-accredited junior high school in the Waru District of Sidoarjo Regency. With the Covid-19 pandemic, academic activities must be conducted online or via the internet. Being online necessitates the application of technology, one of which is the employment of SBS Exam. After conducting interviews and observations, it was discovered that the prototype of the SBS Exam application had various flaws, including a lack of a user-friendly display, high lighting and contrast, unappealing application colors, and several inconsistent and inaccessible buttons. To address this issue, interviews and assessments of the SBS Exam application's operation were conducted, and the problem was then solved by rebuilding the interface on the prototype using the Double Diamond Design approach and usability testing. A usability testing measuring instrument with indicators of learnability, efficiency, memorability, error, and satisfaction is used to calculate the initial evaluation. The results reveal that the average data is low at 2.89, which is considered poor. As a result, the best answer to these issues is to rebuild the SBS Exam application's interface using the Double Diamond Design technique, which consists of four stages: explore, define, develop, and deliver. Questionnaires were provided to 30 respondents, 15 teachers and 15 students, during the testing of the prototype on the SBS Exam application. The average after redesigning the application is 4.24 with an 84.96 percent percentage, indicating that the redesign solution in the SBS Exam application is able to convey the interface design extremely well.